Verification And Validation Of Cfd Software By Onera, Dlr, Airbus For Helicopter Fuselages - Rottmann, L. (My University, 2024)
An extended stencil in Green-Gauss reconstruction and the matrix-free GMRES block Jacobi method are recent advances in CFD, which have been implemented into the new CFD software by ONERA, DLR and Airbus (CODA). The GOAHEAD helicopter fuselage configuration, which was measured in the wind tunnel, is computed with CODA and compared against results generated with DLR's legacy flow solvers FLOWer and TAU.